(untitled) (Revista Brasileira Multidisciplinar, 2008)
Adoption includes changes to both the child and the adoptive home. Seeking to know the experiences regarding adoption, the couple and the family’s experiences, two adoptive mothers were interviewed. The results indicate that the integration of the adopted child was carried out in a positive way, filling an apparent empty spot, and the adopted child was considered responsible for family harmony.